Management and Multiple Large Shareholders Impact Listed on FnB Firms' Transparency - Rashid, Abdul (Malacca: Journal of Management and Business Development, 2025)
Several researches have been conducted that aim to give a better explanation of audit quality, the majority of which are investigating the influence auditor and his work can have on the quality of his work. Contrastingly, this study seeks to investigate how those factors outside the influence of the auditor can affect the quality of his work. we simultaneously investigate how multiple large shareholders and management performance affect audit quality. Our study was conducted on the 32 food and beverage firms listed on IDX at the end of the financial year 2020. The binary logistic regression test revealed that there is a positive and significant relationship between management performance and audit quality, also, a positive but insignificant relationship exists between multiple large shareholdings and audit quality. This study, therefore, indicates that companies whose management is doing well tend to present more truthful financial statements and information to the auditor over the non-performing ones.